The “gender ideology” and the mediatic onslaught: critique of a fallacious discourse - Arce, Leonardo (Nomadías, 2018)
The present article seeks to analyze the mediatic phenomenon resulting from the performance of the group CitizenGO, which in 2017 made a mediatic staging using the so-called “bus of freedom” as a tool to make visible the demand of the evangelical world against the principles of gender theory and the theory of progressive autonomy in children. For this, the article analyzes and stresses the main arguments of the spokeswoman of the group, calling into question the report of the magazine The New Atlantis and showing that, underlying all the speech that arises after the “preferential right of parents”, there is not but a deep fear of difference and a deep love for ignorance.